Water quality index analysis in Kim-Kim River: Effects of Covid-19 movement control order - Mohiyaden H.A.; Sidek L.M.; Noh S.M.; Selamat M.K.; Marufuzzaman M. (Institute of Physics, 2024)
Movement Control Order (MCO) and Conditional Movement Control Order (CMCO) has been implemented throughout the country to reduce the effect of the COVID-19 outbreak. During MCO, several activities, including anthropogenic activities, are not allowed to be operated. Kim-Kim River, which receives most of the effluent from the industrial area, is chosen as a study area for investigating the impact of MCO toward its water quality trends. The results showed that the Water Quality Index (WQI) has improved from Class IV before MCO to Class III during MCO at the upstream of Kim Kim river. Overall, Kim-Kim river water quality has been developed by 19% during MCO. Although from the previous 10 years water quality trends confirm that Kim Kim River is categorised as a polluted river, with the continuation of MCO and the new norm of COVID19, the WQI are expected to be improved. Published under licence by IOP Publishing Ltd.